Prevalence and Distribution of Lesions in the Nasal Bones and Mandibles of a Sample of 144 Riding Horses - Lucia Pérez-Manrique; Karina León-Pérez; Emmanuel Zamora-Sánchez; Sarah Davies; Christopher Ober; Bethany Wilson; Paul McGreevy (Animals, 2020)
Restrictive nosebands are used in equestrian sports to hold the bit in place and reduce mouth-opening, a response that can attract penalties in some sports and is thought to reduce the rider’s control of the horse. Sustained pressure from such tightly fitted (restrictive) nosebands denies normal behaviour and thus, causes frustration and distress that can jeopardise horse welfare. It also may push the cheek against the molar teeth, compress soft tissues including blood vessels and nerves, and possibly induce chronic changes to underlying bone. This study of mature cavalry horses (n = 144) was designed to explore relationships between visual and palpable damage to structures that underlie the nosebands of horses and any related bony changes in those horses as evidenced by radiography. Working independently of each other, two researchers inspected the horses for visual changes and palpable changes before the horses were radiographed. The radiographs were assessed by a separate pair of veterinary radiologists, again working independently of each other. Among the current population of horses, 37.5% had one or more radiographic changes to the nasal bones according to both radiologists, and 13.8% had one or more radiographic changes to the mandible. For nasal bones, the two radiologists reported bone deposition in 6.9% and 8.3% of the horses and bone thinning in 33.3% and 56.9% of the horses, respectively. By palpation, they found that 82% and 84% of the horses had palpable bone deposition of the nasal bones and 32% and 33.4% had palpable bone thinning. For the mandibles, the radiologists reported increased bone deposition in 18.8% and 32.6% of the horses but no bone thinning. By palpation, the two examiners reported 30.6% and 32.7% of the horses had palpable bone deposition and 10.4% and 11.1% had palpable bone thinning. This is the first report of lesions to the mandible at this site and this article presents the first confirmation of bony lesions at the site typically subjected to pressure from restrictive nosebands. These results suggest that radiographic bone thinning is more apparent in the nasal bones of riding horses than in the mandible and that both palpable and radiographic bone deposition are more likely in the mandible than in the nasal bones. That said, we note that the current study provides no evidence of a causal link between any piece of gear or its putative tightness and the lesions in these anatomical locations. Further studies are needed to identify risk factors for these clusters of lesions. The inadvertent deformation of bones in the horse’s head for competitive advantage is difficult to justify on ethical grounds.